Home Variables as Determinant of Students' Attitude towards Examination Malpractice in Uyo Senatorial District of Akwa Ibom State, Nigeria - Evans, G. U.; Umoinyang 1. E.; Ekim, R.E.D (African Journal of Behavioural and Scale Development Research, 2020)
The causal relationship of some home variables as determinant of senior secondary Il students' attitude towards examination malpractice was investigated. This work examined the extent to Which home variables (parents' marital status, parenting style, moral value and parent's socio-economic status) relatively and collectively contribute to students' attitude towards examination malpractice. The research design was the ex-post facto design, the multistage sampling approach uns employed for the study. A total of 450 senior secondary school Il students drawn from 15 schools in nine LGAs within Uyo Senatorial District responded to the research instrument named determinant of students' attitude towards examination malpractice questionnaire. Through the construction of path model, significant pathways were identified and used for the study. The most meaningful causal paths, direct and indirect effects were established. The result that, of the four predictor variables hypothesized, two variables (moral value and parenting style) significantly exerted direct effect on students' attitude toward examination malpractice with parenting style the highest proportion (17.68%) of total direct effect, while moral value had (9.13 of the total direct effect. It was discovered that home variables are strong determinants of students' attitude towards examination malpractice.